Carbon initiator modified resin composition and application thereof

By using a carbon-based initiator-modified resin composition in printed circuit board (PCB) materials, a carbon-based initiator with an asymmetric carbon-carbon bond structure is used to solve the problem of insufficient thermal performance of the existing materials, and the mechanical properties and thermal stability of the materials are significantly improved.

CN119591799APending Publication Date: 2025-03-11NANYA NEW MATERIAL TECH JIANGXI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411738632.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The thermal performance of existing printed circuit board (PCB) materials is insufficient, and the commonly used peroxidation radical initiator has poor thermal stability, which is easy to decompose and produce harmful gases, affecting the anti-aging performance of the material.

Method used

By introducing an asymmetric carbon-carbon bond structure containing benzene ring and strong electron-absorbing groups -NO2 and SO3H into the carbon-based initiator, the intermediate carbon-carbon bonds are ruptured, forming stable and active free radicals, reducing side reactions, and improving the mechanical properties of the material.

Benefits of technology

The impact strength and tensile strength of the metal-covered foil laminate are significantly improved, and the advantages of low thermal expansion coefficient and high elastic modulus are given to the metal-covered foil laminate are given.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses a carbon initiator modified resin composition which is characterized by comprising the following components in parts by weight: 0.5-3 parts of a carbon initiator; 60 to 100 parts of bismaleimide resin; 40 to 80 parts of polyphenyl ether resin; 30 to 50 parts of triallyl isocyanurate resin; 15 to 25 parts of a cross-linking agent; the carbon initiator is shown as a structural formula 1 or a structural formula 2. The invention also discloses an application of the composition. Based on the technical improvement of the invention, the components are beneficial to improving the impact strength and tensile strength of the metal foil-clad laminated board, and also beneficial to endowing the metal-clad plate with the advantages of low thermal expansion coefficient, high elastic modulus and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of resin materials, and in particular to a carbon-based initiator modified resin composition and application thereof. Background Art

[0002] Printed circuit boards (PCBs) play a vital role in modern electronic devices. They are not only the support for electronic components, but also the bridge for electrical connections between components. As electronic devices develop towards high performance and miniaturization, the thermal performance of printed circuit boards (PCBs) becomes particularly important.

[0003] At present, the commonly used initiators mainly include peroxide free radical initiators and carbon-carbon free radical initiators. Peroxide free radical initiators such as peroxides and azo compounds have the ability to efficiently initiate polymerization reactions, but their disadvantages are poor thermal stability and easy decomposition to produce oxygen, which affects the anti-aging performance of the material.

[0004] In addition, these initiators may release harmful gases during use, posing a potential threat to the environment and operators. In contrast, carbon-based initiators exhibit higher stability and safety. This type of initiator does not contain oxygen, and the processed polymer has strong anti-aging and anti-oxidation capabilities, which are suitable for polymer cross-linking or grafting reactions that require higher temperatures. Carbon-based initiators can not only effectively improve the flame retardant properties of materials, but also enhance physical and mechanical properties. At the same time, they have the advantages of being non-toxic, smoke-suppressing, and low-cost, and have become the first choice of more and more copper clad laminate manufacturers.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] One of the purposes of the present invention is to provide a carbon-based initiator modified resin composition which not only has excellent mechanical properties such as impact resistance and outstanding tensile strength, but also has advantages such as dimensional stability and chemical stability and excellent heat resistance.

[0007] The second object of the present invention is to provide an application of a carbon-based initiator modified resin composition, which is beneficial to improving the mechanical properties of metal-clad laminates such as impact resistance and tensile strength, and is also beneficial to giving the metal-clad laminates advantages such as high thermal conductivity, low thermal expansion coefficient and high elastic modulus.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] A carbon-based initiator modified resin composition comprises the following components in parts by weight:

[0010] 0.5-3 parts of carbon-based initiator;

[0011] 60-100 parts of bismaleimide resin;

[0012] 40-80 parts of polyphenylene ether resin;

[0013] 30-50 parts of triallyl isocyanurate resin;

[0014] 15-25 parts of cross-linking agent;

[0015] The carbon-based initiator is shown in the following structural formula 1 or formula 2:

[0016]

[0017]

[0018] Wherein R1 or R2 is any one of hydrogen, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C12 cycloalkyl, and substituted or unsubstituted C5-C30 aryl.

[0019] In a preferred embodiment of the present invention, the carbon-based initiator is shown in the following structural formula 3 or formula 4:

[0020]

[0021] The carbon-based initiator is prepared by reacting an iron catalyst, a ligand, a coupling agent and an alkaline compound in an organic solvent to obtain an initiator as described in structural formula 3 or formula 4.

[0022] The coupling agent is silane coupling agent KH-570, the ligand is tricyclohexylphosphine, the catalyst is iron powder, the alkaline compound is sodium hydroxide, the organic solvent is toluene solution, and the reaction is carried out at 80°C to obtain the product.

[0023] Preferably, the catalyst is 0.03-0.1 equivalent, the ligand is 0.03-0.1 equivalent, the coupling agent is 0.1-0.5 equivalent, the basic compound is 1.0-2.0 equivalent, and the organic solvent concentration is 0.20-30 mol / L.

[0024] In a preferred embodiment of the present invention, the bismaleimide resin has a structure as shown in Formula 5 below:

[0025]

[0026] R1 in Formula 5 is any structure among the structures shown in the following Structural Formulas 6 to 14:

[0027]

[0028] Formula 6 to Formula 14;

[0029] R2 in Formula 5 is any structure among the structures shown in Structural Formulas 15-23:

[0030]

[0031] Formula 15-Formula 23.

[0032] In a preferred embodiment of the present invention, the bismaleimide resin has a structure as shown in Formula 24 below:

[0033]

[0034] Formula 24.

[0035] In a preferred embodiment of the present invention, the polyphenylene ether resin is a polyphenylene ether resin prepared by end-capping with methacrylate and styrene.

[0036] In a preferred embodiment of the present invention, the triallyl isocyanurate resin has a structure as shown in Formula 25 below:

[0037]

[0038] In a preferred embodiment of the present invention, the crosslinking agent is any one or more of a diene compound, an acenaphthylene compound, a trienyl isocyanurate compound, a multifunctional acrylate compound, a multifunctional methacrylate compound, a multifunctional vinyl compound or a divinylbenzene compound crosslinking agent.

[0039] In a preferred embodiment of the present invention, the carbon-based initiator modified resin composition further comprises a flame retardant and a toughening agent, and the weight proportion of the flame retardant is 10-30 parts;

[0040] The weight proportion of the toughening agent is 5-12 parts.

[0041] In a preferred embodiment of the present invention, the flame retardant is any one or more of decabromodiphenylethane, decabromodiphenyl ether, octabromodiphenyl ether or ethylenebistetrabromophthalimide and tris(tribromophenyl)isocyanurate.

[0042] In a preferred embodiment of the present invention, the toughening agent is any one or more of styrene-butadiene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer or maleic anhydride grafted styrene-butadiene-styrene block copolymer elastomer.

[0043] The invention discloses an application of a carbon-based initiator modified resin composition, wherein the application is to prepare a metal foil-clad laminate for a printed circuit board.

[0044] The initiator described in the present invention is a carbon-carbon bond initiator with an asymmetric structure, characterized in that it contains a benzene ring and strong electron-withdrawing groups -NO2 and SO3H. The inventor innovatively discovered that in this asymmetric carbon-carbon bond structure, only when strong electron-withdrawing groups -NO2 and SO3H are introduced and other non-cyano electron-withdrawing groups are targetedly grafted at both ends can the middle carbon-carbon bond be effectively broken. This design allows a stable free radical containing a benzene ring to be formed on one side, while an active free radical containing -NO2 and SO3H is formed on the other side. Such a structure reduces side reactions such as inhibition and self-polymerization of the initiator free radical, thereby ensuring a high conversion rate of the reactants, a high molecular weight of the product, and excellent mechanical properties.

[0045] Compared with the prior art, the present invention has at least the following beneficial effects:

[0046] The carbon-based catalyst catalytic modified resin composition provided by the present invention modifies the organic resin through a carbon-based initiator (as a filler), thereby significantly improving the overall performance of the composite material, and introducing benzene rings and strong electron-withdrawing groups -NO2 and SO3H into the carbon-based initiator.

[0047] The inventors have found through extensive research that in this asymmetric carbon-carbon bond structure, only when strong electron-withdrawing groups -NO2 and SO3H are introduced and other non-cyano electron-withdrawing groups are targetedly grafted on both ends can the middle carbon-carbon bond be effectively broken. This design allows stable free radicals containing benzene rings to be formed on one side, while active free radicals containing -NO2 and SO3H are formed on the other side. Such a structure reduces the side reactions such as inhibition and self-polymerization of the initiator free radicals, thereby ensuring a high conversion rate of the reactants, a high molecular weight of the products, and excellent mechanical properties.

[0048] Based on the technical improvement of the present invention, the components of the present invention are beneficial to improving the impact strength and tensile strength of the metal-clad laminate, and are also beneficial to giving the metal-clad laminate the advantages of low thermal expansion coefficient and high elastic modulus. DETAILED DESCRIPTION

[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] The following embodiments provide a low dielectric thermosetting resin composition, comprising (a) a carbon-based initiator and (b) a resin composition, wherein:

[0051] Synthesis of the carbon-based initiator in the embodiment: an iron catalyst, a ligand, a coupling agent and an alkaline compound are reacted in an organic solvent, 0.05 equivalent of iron powder, 0.05 equivalent of ligand, 0.1 equivalent of coupling agent, 1.5 equivalent of alkaline compound, and an organic solvent concentration of 0.25 mol / L to obtain (a) a carbon-based initiator.

[0052] The catalyst is iron powder, the coupling agent is silane coupling agent KH-570, the ligand is tricyclohexylphosphine, the alkaline compound is sodium hydroxide, and the organic solvent is toluene solution, and the reaction is performed at 80°C to obtain the product.

[0053] Initiator structure in the embodiment:

[0054] The structure is

[0055]

[0056] The structural formula of the resin composition provided in the embodiment is as follows:

[0057]

[0058] The polyphenylene ether in the embodiment is TPO9500.

[0059] The triallyl isocyanurate resin in the embodiment has the following structural formula:

[0060]

[0061] After bismaleimide, polyphenylene ether resin and triallyl isocyanurate resin are mixed and modified, a carbon-based initiator (as a filler), a flame retardant, a toughening agent and a cross-linking agent are added to obtain a resin glue solution.

[0062] The flame retardant and toughening agent can be added as needed.

[0063] The preparation of the adhesive solution of the present invention by combining with the glass fiber cloth reinforcement material is carried out at room temperature, which greatly shortens the preparation time and improves the production efficiency.

[0064] The preparation of prepregs makes up for the shortcomings of slow curing rate, long curing temperature and time of single resin. The preparation of prepregs can be completed at a temperature of 140-160℃ and a time of 200-300S. After the prepregs are obtained, they are laminated to obtain metal-clad plates with good performance.

[0065] The present invention will be further explained and illustrated by specific embodiments below:

[0066] 1. The specific preparation method of the resin composition of the present invention is as follows:

[0067] A. Add toluene according to the amount in Table 1 into the reactor, turn on the high-speed stirrer at a speed of 1500 rpm, keep stirring continuously and control the tank temperature at 45°C;

[0068] B. Add bismaleimide and polyphenylene ether resin into the reaction kettle according to the formula in Table 1. After the addition is completed, stir for 60 minutes until the resin is completely dissolved to obtain a resin composition.

[0069] 2. The preparation method of the resin glue of the present invention is as follows:

[0070] A. Add toughening agent, flame retardant and filler into the reactor according to the formula in Table 1, turn on the high-speed stirrer at a speed of 1800 rpm, and continue stirring for 60 minutes after the addition is completed;

[0071] B. Add initiator into the reactor according to the formula in Table 1. After adding, start the cooling water circulation and keep the speed at 1500rpm. Control the tank temperature at 45℃ and continue stirring for 180 minutes. The resin glue is ready.

[0072] 3. The method for preparing the prepreg of the present invention is as follows:

[0073] A. The gluing baking temperature is 140℃-160℃, and the gluing speed is 10m / min;

[0074] B. Use 2116E-glass fiberglass cloth;

[0075] C. The prepreg resin content is adjusted according to the required thickness of the metal foil-clad plate;

[0076] 4. The method for preparing the metal foil-clad plate of the present invention is as follows:

[0077] A. The number of prepreg sheets is determined according to the requirements of the metal foil laminated structure. Table 1 shows one of the laminated structures.

[0078] B. The metal foil used for the metal foil-clad board is selected as needed, and the RTF copper foil described in Table 1;

[0079] C. The lamination parameters of the metal foil clad plate are adjusted as required. The lamination conditions described in Table 1 are:

[0080] Vacuum pressure 50Torr; pressure 1.2-1.5MPa; hot plate temperature 150-220℃; curing time 200min.

[0081] The samples in Examples 1-4 and Comparative Examples 1-4 were tested for various properties according to the following methods. The components and data of each example or comparative example are shown in Table 1:

[0082] Tensile strength: According to the standard of IPC-TM-650 2.2.1, the tensile strength of the sample is tested using a universal mechanical testing machine;

[0083] Impact strength: According to the standard of IPC-TM-650 2.4.23, the tensile strength of the sample is tested using a tensile impact testing machine;

[0084] Elastic modulus: According to the standard specified in IPC-TM-650 2.4.24.4, the elastic modulus of the sample is measured using a DMA instrument;

[0085] Thermal expansion coefficient: According to the standard specified in IPC-TM-650 2.4.24, the thermal expansion coefficient of the sample is measured using a TMA instrument;

[0086] Dielectric constant (Dk) and dielectric loss factor (Df): The dielectric constant and dielectric loss factor test methods are in accordance with the test specified in IPC-TM-650 2.5.5.9.

[0087] Table 1:

[0088]

[0089]

[0090] As can be seen from the above table, the components of the present invention are beneficial to improving the impact strength and tensile strength of the metal-clad laminate, and are also beneficial to giving the metal-clad laminate advantages such as low thermal expansion coefficient and high elastic modulus.

Claims

1. A carbon-based initiator modified resin composition, characterized in that: By weight, it includes the following components: 0.5-3 parts of carbon-based initiator; 60-100 parts of bismaleimide resin; 40-80 parts of polyphenylene ether resin; 30-50 parts of triallyl isocyanurate resin; 15-25 parts of cross-linking agent; The carbon-based initiator is shown in the following structural formula 1 or formula 2: Wherein R1 or R2 is any one of hydrogen, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C12 cycloalkyl, and substituted or unsubstituted C5-C30 aryl.

2. A carbon-based initiator modified resin composition according to claim 1, characterized in that: The carbon-based initiator is shown in the following structural formula 3 or formula 4: The carbon-based initiator is prepared by reacting an iron catalyst, a ligand, a coupling agent and an alkaline compound in an organic solvent to obtain an initiator as described in structural formula 3 or formula 4.

3. A carbon-based initiator modified resin composition as claimed in claim 2, characterized in that: The coupling agent is silane coupling agent KH-570, the ligand is tricyclohexylphosphine, the catalyst is iron powder, the alkaline compound is sodium hydroxide, the organic solvent is toluene solution, and the reaction is carried out at 80°C to obtain; The catalyst is 0.03-0.1 equivalent, the ligand is 0.03-0.1 equivalent, the coupling agent is 0.1-0.5 equivalent, the basic compound is 1.0-2.0 equivalent, and the organic solvent concentration is 0.20-30 mol / L.

4. A carbon-based initiator modified resin composition as claimed in claim 1, characterized in that: The bismaleimide resin has a structure as shown in Formula 5 below: R1 in Formula 5 is any structure among the structures shown in the following Structural Formulas 6 to 14: R2 in Formula 5 is any structure among the structures shown in Structural Formulas 15-23:

5. A carbon-based initiator modified resin composition as claimed in claim 1, characterized in that: The bismaleimide resin has a structure as shown in Formula 24:

6. A carbon-based initiator modified resin composition as claimed in claim 1, characterized in that: The polyphenylene ether resin is prepared by end-capping with methacrylate and styrene.

7. A carbon-based initiator modified resin composition as claimed in claim 1, characterized in that: The triallyl isocyanurate resin has a structure as shown in Formula 25 below: Formula 25.

8. A carbon-based initiator modified resin composition as claimed in claim 1, characterized in that: The crosslinking agent is any one or more of a diene compound, an acenaphthylene compound, a trialkenyl isocyanurate compound, a multifunctional acrylate compound, a multifunctional methacrylate compound, a multifunctional vinyl compound or a divinylbenzene compound crosslinking agent.

9. A carbon-based initiator modified resin composition according to claim 1, characterized in that: The carbon-based initiator modified resin composition further comprises a flame retardant and a toughening agent, wherein the weight proportion of the flame retardant is 10-30 parts; The weight proportion of the toughening agent is 5-12 parts.

10. An application of a carbon-based initiator modified resin composition as claimed in any one of claims 1 to 9, characterized in that: The application is to prepare metal foil-clad laminates for printed circuit boards.